High-strength 7-series rare earth doped aluminum alloy and processing technology thereof
Patent Information
- Application Number
- CN202611395389.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-09
- Publication Date
- 2026-10-27
AI Technical Summary
[0003]本发明的目的是针对现有技术中的不足,提供一种高强7 系稀土掺杂铝合金及其加工工艺,以高含量 Zn、Mg、Cu 作为主强化组元,搭配 Zr-Mn-Cr 三元复合晶粒稳定微量元素与 Ce-La 复合轻稀土微合金化,限定各元素配比系数;通过铸锭、双级均匀化退火、大挤压比热挤压、高温固溶快速水淬,室温可控冷预变形,再耦合 130-160℃区间双级分级低温应变时效,规避传统二级时效高温导致强化相粗化、常规冷变形量不足强化效果弱的缺陷,实现弥散强化、位错强化与纳米析出沉淀强化三重协同增效,成品屈服强度突破800MPa,同时保留合格塑性与耐剥落腐蚀性能,适用于航空航天主承力构件、军工重载轻量化结构件等超高强度铝合金应用场景
[0021]本发明通过高载量 Zn-Mg-Cu 主强化体系搭配 Zr-Mn-Cr 三元复合晶粒稳定元素、Ce-La 复合稀土微合金化;Al3Zr 弥散相协同 Mn、Cr 弥散粒子双重钉扎晶界,抑制挤压与固溶阶段晶粒粗化,提升组织热稳定性。创新采用全低温区间双级时效,两级时效温度均控制在 130~160℃,规避传统二级时效超 165℃引发的 η' 相粗化、强度衰减缺陷。适度提高冷预变形量至 3.5%~7.5% 区间,在不产生明显基体微损伤前提下大幅提升位错密度。采用 “室温冷预变形(拉伸 / 轧制兼容)+ 双级低温应变时效” 耦合强化机制,棒材选用拉伸、板材选用轧制两种冷加工方式;利用冷变形引入高密度位错搭配 Al3Zr 相作为η' 相双重非均匀形核位点,实现弥散强化、位错形变强化与纳米析出沉淀强化三重叠加。精准控制析出相尺寸、体积分数与晶界微观结构,稳定实现屈服强度 800MPa 以上超高强度,同时保留工程可用塑性与耐蚀性能。本发明拉伸、轧制两种冷预变形模式适配全部主流挤压制品,整套工艺依托现有铝加工成熟设备即可实现工业化量产,在航空航天主承力构件、军工重载轻量化结构件领域具备广阔应用前景。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of aluminum alloy technology, and in particular to a high-strength 7-series rare earth-doped aluminum alloy and its processing technology. Background Technology
[0002] 7xxx series Al-Zn-Mg-Cu aluminum alloys achieve precipitation strengthening through GP zone and metastable η'(MgZn2) nano-precipitates, making them the most widely used metallic materials for lightweight, ultra-high-strength load-bearing components. Existing commercially available 7075, 7050, and 7085 aluminum alloys, after traditional T6 single-stage peak aging and RRA re-aging processes, exhibit yield strengths concentrated in the 540–770 MPa range. Existing research on deformation aging to improve the strength of 7-series aluminum alloys generally suffers from poor process stability and low batch repeatability; low cold pre-deformation amounts and a single deformation mode, lacking Zr-Mn and Cr synergistic grain refinement and stabilization; and excessively high secondary aging temperatures leading to coarsening of the precipitates. This makes them unsuitable for simultaneous application to various extruded products such as extruded bars and sheets, hindering the stable breakthrough of the 800 MPa strength threshold and failing to meet the requirements of ultra-lightweight load-bearing components in high-end equipment. Summary of the Invention
[0003] The purpose of this invention is to address the shortcomings of existing technologies by providing a high-strength 7-series rare-earth-doped aluminum alloy and its processing technology. It uses high-content Zn, Mg, and Cu as the main strengthening components, combined with Zr-Mn-Cr ternary composite grain-stabilizing trace elements and Ce-La composite light rare-earth microalloying, with limited element ratios. Through ingot casting, two-stage homogenization annealing, high-specific-heat extrusion, high-temperature solution treatment and rapid water quenching, room-temperature controllable cold pre-deformation, and then coupled with two-stage graded low-temperature strain aging in the 130-160℃ range, it avoids the defects of traditional two-stage aging, such as coarsening of the strengthening phase and insufficient strengthening effect due to conventional cold deformation. This achieves a triple synergistic effect of dispersion strengthening, dislocation strengthening, and nano-precipitation strengthening, resulting in a finished product with a yield strength exceeding 800MPa while retaining adequate plasticity and resistance to exfoliation corrosion. It is suitable for ultra-high-strength aluminum alloy applications such as aerospace main load-bearing components and heavy-duty lightweight structural parts in military applications.
[0004] To achieve the above-mentioned objectives, the present invention adopts the following technical solution:
[0005] In a first aspect, the present invention provides a high-strength 7-series rare-earth-doped aluminum alloy with a yield strength ≥800MPa, which is composed of the following components by mass percentage: Zn: 9.2–12.5%, Mg: 2.6–3.8%, Cu: 1.4–2.8%, Mn: 0.15–0.35%, Cr: 0.08–0.22%, Zr: 0.05–0.18%, Fe≤0.18%, Si≤0.12%, Ce + La composite rare earth: 0.03–0.12%, the remaining components are Al and unavoidable impurities; The Zn / Mg mass ratio is (3.0–4.2):1, the Cu / Mg mass ratio is (0.5–0.8):1, the total mass fraction of the three main strengthening elements Zn, Mg and Cu is 13.5%–16.5%, and the mass ratio of Ce to La is 1:1.
[0006] Preferably, the high-strength 7-series rare earth-doped aluminum alloy of the present invention is composed of the following components by mass percentage: Zn: 10.0-11.8%, Mg: 3.0-3.6%, Cu: 1.8-2.5%, Mn: 0.20-0.30%, Cr: 0.12-0.18%, Zr: 0.08-0.14%, Ce+La composite rare earth: 0.05-0.09%, Fe≤0.15%, Si≤0.10%, total impurities ≤0.15%, and the balance being metallic aluminum.
[0007] In this invention, Mn and Cr form dispersed Al6Mn and Al7Cr particles in the alloy; Zr forms a nano-Al3Zr dispersed phase. These three elements synergistically pin grain boundaries and subgrain boundaries, strongly inhibiting dynamic recrystallization and grain recovery growth during extrusion and high-temperature solution processes, significantly improving the high-temperature structural stability of the alloy. The Al3Zr phase can also serve as a heterogeneous nucleation core for η' precipitates, further increasing the precipitate density and simultaneously improving the alloy's strength and corrosion resistance. The Ce-La composite rare earth element purifies the melt, refines the as-cast grains, reduces dendrite segregation, optimizes the precipitate distribution, and weakens the destructive effect of continuous grain boundary precipitation on corrosion resistance.
[0008] Secondly, the present invention provides a processing technology for the above-mentioned high-strength 7-series rare-earth-doped aluminum alloy, comprising the following steps: S1. Under an inert atmosphere, raw materials are weighed according to the mass percentage of each element in the aluminum alloy and then smelted and cast to obtain ingots. S2. Perform two-stage homogenization treatment on the ingot; S3, high specific heat extrusion molding, to obtain dense fiber textured extruded profiles; S4. The extruded material is subjected to solution quenching treatment to prepare a supersaturated solid solution billet; S5. Pre-deform the supersaturated solid solution billet; S6, two-stage artificial aging, with both aging temperatures controlled at 130-160℃, yields a finished ultra-high strength aluminum alloy.
[0009] Furthermore, the two-stage homogenization process for the ingot involves: holding the ingot at 350–380℃ for 8–12 hours, then raising the temperature to 460–480℃ and holding it therefore for 6–10 hours, followed by furnace cooling to room temperature. This two-stage homogenization process can effectively eliminate dendritic segregation within the ingot, reduce the content of non-equilibrium eutectic phases, and avoid the problems of insufficient element re-dissolution or overheated grain growth caused by single-stage homogenization.
[0010] Further, the extrusion process parameters for step S3 are as follows: the ingot is preheated at 410–440℃ for 3–5 hours before extrusion; the extrusion cylinder is at 400–430℃, and the die at 390–420℃; the extrusion ratio is 25:1–50:1; the extrusion discharge line speed is 1.5–4 m / min; and the material is air-cooled to room temperature after extrusion. A large extrusion ratio is used to break up coarse dendrites in the as-cast state, forming a continuous and dense fibrous structure, which improves the subsequent precipitation behavior of precipitated phases.
[0011] Further, step S4, the solution quenching process, involves holding the extruded material at 472–482℃ for 90–150 minutes, and immediately quenching it in water at a cooling rate ≥25℃ / s. This ensures that the main alloying elements are fully dissolved and incorporated into the aluminum matrix, while simultaneously suppressing precipitation through a high cooling rate, resulting in a highly supersaturated solid solution.
[0012] Furthermore, the pre-deformation treatment in step S5 employs either room temperature uniaxial tensile pre-deformation or room temperature cold rolling pre-deformation, with the effective plastic deformation amount uniformly controlled between 3.5% and 7.5%. If the deformation amount is below 3.5%, the dislocation density improvement is insufficient, and the strain-aging strengthening gain is weak; if the deformation amount exceeds 7.5%, micropores and microcracks are easily generated in the matrix, the plastic cliff decreases, and the material loses its engineering value. Tensioning is used for bars, and rolling is used for plates, compatible with various extruded products, expanding the application range of the process.
[0013] When the extruded products are bars or round profiles, uniaxial tensile pre-deformation is used, with a preferred tensile deformation of 4.5% to 6.5% and a tensile strain rate of 0.05 to 0.15 s. - ¹; When the extruded products are sheets or flat wide profiles, cold rolling pre-deformation is used. The equivalent plastic strain of the total rolling reduction is controlled at 4.5% to 6.5%, and the rolling deformation rate is 0.02 to 0.10 s. - ¹.
[0014] Furthermore, in step S5, the two-stage artificial aging process is performed, with both stages limited to a temperature range of 130–160°C. First-stage low-temperature pre-aging: holding at 130-145℃ for 24-36 hours to fully analyze and separate ultrafine GP regions and primary η' phase; Second-stage low-temperature stabilization aging: holding at 146~160℃ for 5~9h, adjusting the η' phase size to avoid high-temperature coarsening; After aging, the furnace is cooled to room temperature. The optimal aging parameters are 138℃ for 30 hours, followed by 152℃ for 6 hours.
[0015] This invention limits both stages of aging to the 130-160℃ range, avoiding the defects of traditional two-stage aging exceeding 165℃, which leads to the coarsening of the η' phase and the transformation to the equilibrium η phase. The first stage, with its long-term low temperature, enables the extensive nucleation of the GP zone and the primary η' phase. The second stage, with its medium-low temperature and short-term heat preservation, finely controls the size of the precipitated phase, preserving plasticity while ensuring high strength, and simultaneously narrowing the grain boundary precipitate-free zone, thus improving corrosion resistance.
[0016] The microstructure of the finished aluminum alloy prepared by the composition and process of this invention is as follows: uniformly distributed nano-Al3Zr dispersed phase, average size of nano-η'(MgZn2) precipitates ≤2.6nm, total precipitate integral ≥12.5%, no coarse equilibrium η phase, and grain boundary precipitate band width ≤18nm; finished product performance indicators: yield strength Rp0.2≥800MPa, tensile strength Rm≥850MPa, elongation after fracture A≥4.0%; exfoliation corrosion rating ≥EB level, electrical conductivity ≥28% IACS.
[0017] The core strengthening phase of the 7-series ultra-high strength aluminum alloy of this invention is η'(MgZn2) nano-precipitates. The volume fraction of the precipitates is determined by the content of Zn, Mg and Cu in the alloy and is controlled by the entire process of melting, casting, homogenization, extrusion and heat treatment. After the alloy composition is determined, the theoretical maximum volume fraction of the strengthening phase is fixed, and the process directly determines the size, quantity, distribution uniformity and grain boundary structure of the precipitates.
[0018] When using only traditional single / double-stage aging without cold pre-deformation, the number of nucleation sites inside the matrix is limited, the η' phase precipitation density is low and prone to local coarsening, and the strengthening effect has a clear upper limit. When the cold pre-deformation amount is less than 3.5%, the increase in dislocation density is insufficient, and the strain aging strengthening gain is weak. If the secondary aging temperature exceeds 160℃, the metastable η' phase coarsens rapidly and transforms into the equilibrium η phase, the strengthening effect drops significantly, and the plasticity deteriorates simultaneously. When relying solely on cold deformation without graded low-temperature aging, the dislocation energy storage is too high and easily leads to recovery, and the size of the precipitated phase is out of control. Single tensile pre-deformation is not suitable for extruded sheet products, and the process application range is narrow. When Zr is lacking, the grains are prone to recovery and growth during high-temperature extrusion and solution treatment, the dispersion pinning effect is insufficient, and the strength and thermal stability decrease. When the cold deformation amount exceeds 7.5%, micropores and microcracks are easily formed inside the matrix, and the material plasticity is greatly reduced, losing its engineering value.
[0019] This invention adds Zr to generate nano-Al3Zr dispersed particles, which form a composite pinning system with Mn and Cr dispersed phases, significantly inhibiting dynamic recrystallization. Al3Zr can serve as the η' phase precipitation nucleus, further increasing the density of the strengthening phase. The aging process is controlled within the range of 130–160℃, with a first-stage long-term low-temperature sufficient nucleation and a second-stage medium-low-temperature short-term controlled growth, suppressing η phase coarsening from the root. Cold pre-deformation is limited to 3.5%–7.5%, moderately increasing the deformation range to maximize dislocation density within a controllable plasticity loss range. First, large dendrites in the cast state are broken by high-specific-heat extrusion to form a continuous and dense fibrous structure along the extrusion direction. High-temperature solution solidification and water quenching construct a highly supersaturated solid solution. Corresponding cold working methods are matched for different extruded products: bars are stretched and plates are rolled. Room-temperature controllable deformation introduces a high-density uniform dislocation network, providing a large number of nucleation nuclei for the nano-η' phase. Then, long-term low-temperature pre-aging at 130–145℃ promotes the formation of ultrafine GP regions and primary η' phases. Uniform precipitation of the precipitate, along with precise control of the precipitate size through short-term, medium-low temperature aging at 146–160℃, significantly increases the volume fraction of the nano-reinforcing phase and refines the precipitate size. Simultaneously, it narrows the grain boundary precipitate-free zone, achieving ultra-high strength, adequate plasticity, and corrosion resistance. The Ce-La composite rare earth element purifies the melt and refines the as-cast grains, further optimizing the precipitate distribution and mitigating the detrimental effect of continuous grain boundary precipitation on corrosion resistance.
[0020] Ce-La composite rare earth purifies the melt and refines the as-cast grains, further optimizing the distribution of precipitated phases and reducing the damage to corrosion resistance caused by continuous precipitation at grain boundaries.
[0021] This invention employs a high-loading Zn-Mg-Cu main strengthening system combined with Zr-Mn-Cr ternary composite grain stabilizing elements and Ce-La composite rare earth microalloying. The Al3Zr dispersed phase, along with Mn and Cr dispersed particles, synergistically pins grain boundaries, suppressing grain coarsening during extrusion and solution treatment, thus enhancing the thermal stability of the microstructure. It innovatively utilizes a two-stage aging process across the entire low-temperature range, with both stages controlled at 130–160℃, avoiding the η' phase coarsening and strength reduction defects caused by traditional two-stage aging exceeding 165℃. The cold pre-deformation amount is moderately increased to the range of 3.5%–7.5%, significantly improving dislocation density without causing significant micro-damage to the matrix. This invention employs a coupled strengthening mechanism of "room temperature cold pre-deformation (tensioning / rolling compatible) + two-stage low-temperature strain aging," utilizing both stretching and rolling cold working methods for bars and plates. It leverages the high-density dislocations introduced by cold deformation, combined with the Al3Zr phase as dual heterogeneous nucleation sites for the η' phase, to achieve a triple superposition of dispersion strengthening, dislocation deformation strengthening, and nanoprecipitation strengthening. Precise control of the precipitate size, volume fraction, and grain boundary microstructure ensures a stable yield strength exceeding 800 MPa, while retaining engineering-grade plasticity and corrosion resistance. This invention's stretching and rolling cold pre-deformation modes are compatible with all mainstream extruded products. The entire process can be industrialized using existing mature aluminum processing equipment, demonstrating broad application prospects in aerospace main load-bearing components and heavy-duty lightweight structural parts for military applications. Detailed Implementation
[0022] To further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, and not for limiting the scope of the claims of the present invention.
[0023] Example 1 (Extruded bar stock, tensile pre-deformation) The high-strength 7-series rare earth-doped aluminum alloy, by mass percentage, comprises: Zn 11.2%, Mg 3.3%, Cu 2.2%, Mn 0.25%, Cr 0.15%, Zr 0.12%, Ce+La rare earth 0.07% (Ce:La mass ratio is 1:1), Fe 0.12%, Si 0.08%, with the remainder being Al and unavoidable impurities.
[0024] Under an inert atmosphere, raw materials are weighed according to the mass percentage of each element in the aluminum alloy and then smelted and cast to obtain ingots; The ingots with the above composition were homogenized, and then held at 360°C for 10 hours. The temperature was then increased to 470°C and held for 8 hours. Finally, the ingots were cooled to room temperature in the furnace. After homogenization, the ingot was preheated at 420℃ for 4 hours, and then extruded. The extrusion cylinder was at 420℃ and the die at 400℃. The extrusion ratio was 35:1 and the extrusion discharge line speed was 2m / min. After extrusion, the ingot was air-cooled to room temperature. The extruded material was subjected to solution quenching treatment, held at 478℃ for 120 minutes, and then quenched in water at a quenching cooling rate of 35℃ / s. Room temperature uniaxial tensile pre-deformation was used, with a deformation of 5.5% and a strain rate of 0.10 s⁻¹. - ¹; Aging treatment: Level 1 aging is maintained at 138℃ for 30 hours, and Level 2 aging is maintained at 152℃ for 6 hours.
[0025] Example 2 The difference from Example 1 is as follows: The high-strength 7-series rare earth-doped aluminum alloy, by mass percentage, comprises: Zn 10.1%, Mg 3.0%, Cu 1.9%, Mn 0.22%, Cr 0.13%, Zr 0.09%, Ce+La rare earth 0.05% (Ce:La mass ratio is 1:1), Fe 0.12%, Si 0.08%, with the remainder being Al and unavoidable impurities.
[0026] Cold rolling pre-deformation was performed with a deformation amount of 4.5% and a rolling deformation rate of 0.05 s. -1 ; Aging treatment: Level 1, 132℃ for 34 hours; Level 2, 148℃ for 8 hours.
[0027] Example 3 The difference from Example 1 is as follows: The high-strength 7-series rare earth-doped aluminum alloy, by mass percentage, comprises: Zn 11.7%, Mg 3.5%, Cu 2.4%, Mn 0.28%, Cr 0.17%, Zr 0.14%, Ce+La rare earth 0.09% (Ce:La mass ratio is 1:1), Fe 0.12%, Si 0.08%, with the remainder being Al and unavoidable impurities.
[0028] Cold rolling pre-deformation was employed, with a deformation amount of 6.5% and a rolling deformation rate of 0.03 s. -1 ; Aging treatment: Level 1, 143℃ for 26 hours; Level 2, 156℃ for 5 hours.
[0029] Comparative Example 1 The difference from Example 1 is as follows: The high-strength 7-series rare earth-doped aluminum alloy, by mass percentage, comprises: Zn 11.2%, Mg 3.3%, Cu 2.2%, Mn 0.25%, Cr 0.15%, Ce+La rare earth 0.07% (Ce:La mass ratio is 1:1), Fe 0.12%, Si 0.08%, with the remainder being Al and unavoidable impurities.
[0030] Comparative Example 2 The difference from Example 1 is as follows: The extruded material is subjected to solution quenching and then directly subjected to two-stage aging at 138℃ / 30h + 152℃ / 6h without any room temperature cold pre-deformation.
[0031] Comparative Example 3 The difference from Example 1 is as follows: Aging treatment: Level 1 aging is maintained at 138℃ for 30 hours, and Level 2 aging is maintained at 170℃ for 6 hours.
[0032] Comparative Example 4 The difference from Example 1 is as follows: Room temperature uniaxial tensile pre-deformation was used with a deformation amount of 2% and a strain rate of 0.10 s⁻¹. - ¹; Comparative Example 5 It uses commercially available standard 7085 extruded bars and adopts existing industrialized RRA re-aging heat treatment, without cold pre-deformation process.
[0033] The testing schemes for the mechanical properties, microstructure, exfoliation corrosion, and electrical conductivity of each sample in this invention are as follows: (1) Room temperature tensile mechanical property test, in accordance with GB / T 228.1-2021 "Metallic materials, tensile testing - Part 1: Room temperature test method" (2) Exfoliation corrosion performance test, in accordance with GB / T 22638-2022 "Test method for exfoliation corrosion of aluminum alloy".
[0034] (3) Conductivity test, in accordance with GB / T 12966-2008 "Eddy current test method for conductivity of aluminum alloy".
[0035] (4) Transmission electron microscopy (TEM) microstructure analysis (η' phase size, volume fraction, PFZ width) Table 1 lists the room temperature mechanical properties and microstructure characteristics of each embodiment and comparative example.
[0036] As shown in Table 1, this invention utilizes a Zr-Mn-Cr ternary composite grain stabilization system + a rare earth high-alloying composition system + a two-stage low-temperature aging process at 130–160℃ + a controllable cold pre-deformation coupling process within the range of 3.5%–7.5% to precisely control the size, volume fraction, and grain boundary PFZ width of the nano-Al3Zr dispersed phase and η' precipitate. Examples 1-3 all exhibit yield strengths exceeding 800 MPa, with elongation after fracture ≥3.9%, balancing ultra-high strength and engineering-grade plasticity. Examples without Zr, without strain-induced cold deformation, with low cold deformation, two-stage aging at over 160℃, or traditional commercial alloys cannot simultaneously meet the two core indicators of Rp0.2 ≥800 MPa and elongation ≥4.0%. This verifies the effectiveness of Zr composite trace elements, the two-stage low-temperature aging process at 130–160℃, and the controllable cold pre-deformation coupling process within the 3.5%–7.5% range. The creativity and necessity of the moderate cold pre-deformation range, dual-mode cold pre-deformation and strain aging coupling process.
[0037] Based on the disclosure in the foregoing specification, those skilled in the art can make appropriate changes and modifications to the above embodiments. Therefore, the present invention is not limited to the specific embodiments disclosed and described above, and some modifications and changes to the present invention should also fall within the protection scope of the claims of the present invention. Furthermore, although some specific terms are used in this specification, these terms are only for convenience of explanation and do not constitute any limitation on the present invention.
Claims
1. A high-strength 7-series rare-earth-doped aluminum alloy, characterized in that: By mass percentage, it consists of the following components composition: Zn: 9.2–12.5%, Mg: 2.6–3.8%, Cu: 1.4–2.8%, Mn: 0.15–0.35%, Cr: 0.08–0.22%, Zr: 0.05–0.18%, Fe≤0.18%, Si≤0.12%, Ce + La composite rare earth: 0.03–0.12%, the total mass fraction of Zn, Mg and Cu is 13.5%–16.5%, and the remaining components are Al and unavoidable impurities.
2. The high-strength 7-series rare-earth-doped aluminum alloy according to claim 1, characterized in that: The mass ratio of Zn to Mg is (3.0–4.2):
1.
3. The high-strength 7-series rare-earth-doped aluminum alloy according to claim 1, characterized in that: The mass ratio of Cu to Mg is (0.5-0.8):
1.
4. The high-strength 7-series rare-earth-doped aluminum alloy according to claim 1, characterized in that: The mass ratio of Ce to La is 1:
1.
5. The high-strength 7-series rare-earth-doped aluminum alloy according to claim 1, characterized in that: The high-strength 7-series rare earth-doped aluminum alloy has a yield strength Rp0.2 ≥ 800 MPa, a tensile strength Rm ≥ 850 MPa, and an elongation ≥ 4%.
6. The processing technology for high-strength 7-series rare-earth-doped aluminum alloys according to any one of claims 1 to 5, characterized in that: Includes the following steps: S1. Under an inert atmosphere, raw materials are weighed according to the mass percentage of each element in the aluminum alloy and then smelted and cast to obtain ingots. S2. The ingot is subjected to homogenization treatment. The homogenization treatment process is as follows: the ingot is kept at 350-380℃ for 8-12 hours, then heated to 460-480℃ and kept at 460-480℃ for 6-10 hours, and then cooled to room temperature with the furnace. S3. The homogenized ingot is extruded. The extrusion process is as follows: the extrusion cylinder temperature is 400-430℃, the die temperature is 390-420℃, the extrusion ratio is 25:1-50:1, the extrusion discharge line speed is 1.5-4m / min, and then it is air-cooled to room temperature. S4. The extruded material is subjected to solution quenching treatment to prepare a supersaturated solid solution billet; S5. Perform room temperature pre-deformation treatment on the supersaturated solid solution billet; S6. Aging treatment: keep at 130-145℃ for 24-36 hours, and then keep at 146-160℃ for 5-9 hours.
7. The processing technology according to claim 6, characterized in that: In step S3, the homogenized ingot is preheated before extrusion at a temperature of 410–440°C for 3–5 hours.
8. The processing technology according to claim 6, characterized in that: The solution quenching process in step S4 is as follows: the extruded material is kept at 472-482℃ for 90-150 minutes, and after the holding time is completed, it is quenched in water with a quenching cooling rate ≥25℃ / s.
9. The processing technology according to claim 6, characterized in that: In step S5, when the extruded material is a bar or round profile, the room temperature controllable cold working pre-deformation adopts uniaxial tensile pre-deformation, and the deformation amount of the uniaxial tensile pre-deformation is 4.5% to 6.5%, and the tensile strain rate is 0.05 to 0.15 s. -1 .
10. The processing technology according to claim 6, characterized in that: In step S5, when the extruded product is a sheet or a flat wide profile, the room temperature controllable cold working pre-deformation adopts cold rolling pre-deformation, and the equivalent plastic deformation of the cold rolling pre-deformation is 4.5% to 6.5%, with a rolling deformation rate of 0.02 to 0.10 s. -1 .